Beyond primitivism: indigenous religious traditions and modernity - Olupona, Jacob Kẹhinde (Routledge, 2004)
Introduction / Jacob K. Olupona -- pt I. Modernity and methodology -- pt. II. The Americas -- pt. III. Africa and Asia -- pt. IV. The Pacific Islands.